The effect of distortion of information as a socio-psychological factor of reducing the quality of labor interaction under isolation - I. A. Vakula; E. V. Zvonova; E. V. Scherbakova (Вестник университета)
The relevance of the problem under study is due to the problems that arise in the conditions of remote forms of labor interaction, as well as the role of the manager in creating an effective communication environment. The purpose of the article is to present the results of a study of the effect of information distortion in labor interaction in isolation, statistical and qualitative analysis of the results. The data obtained allow us to say that in the conditions of remote forms of labor interaction, the lack of direct contact leads to the difficulty of understanding the transmitted information, a decrease in job satisfaction, remission of the levels of well-being, activity and mood, which disrupts the quality of labor communication. The study showed that the subjective assessment of the effectiveness of leadership has a great impact on the state of the participants in the labor interaction. To ensure effective interaction of employees, it is necessary to introduce the rules of remote communication: unified, standardized requirements for communication in remote mode that meet the specifics of a particular enterprise; exclusion from communication of all manifestations of negative emotions; use of all range of available means of communication; emotional leadership of the leader.